EFFECT OF COMPLEXITY OF WORK, CAREER DEVELOPMENT, ORGANIZATIONAL COMMUNICATION ON THE PERFORMANCE OF EMPLOYEES - Rini Handayani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
This study aims to examine several factors that can influence employee performance including work complexity, career development, and organizational communication The sample used was 76 Bank “X” employees in Surakarta City. The sampling method uses the survey sampling method. The type of data used is primary data. The data analysis method uses multiple regression with the help of SPSS 23 The coefficient of determination test results shows that the complexity of work, career development and organizational communication can explain employee performance by 50.3% while the remaining 49.7% employee performance will be explained by other factors outside the three research variables. The results of the hypothesis test analysis show the conclusion that work complexity, career development, and organizational communication affect employee performance.